(3GdKhQI GdCeQjcjI (B/s - (3MLQ, LeGd eMehOs ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ddfTQ h GdJhRjY,,s, 2006)
(3jJVef edNU HGddZI GdGfLdjRjI(B.s
(3HHdjhLQGajG (B: (3U(B. 62-63.s
Keywords: (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3JGQjNs -- (3KhQI, (B1775-1783s; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3CMhGd SjGSjIs -- 1775-1783